The Yangtze and the Rhine, two Major Rivers Systems: An Introduction - Klemann, Hein A.M. (TSEG - The Low Countries Journal of Social and Economic History, 2024)
This introduction to the articles about the Rhine and the Yangtze as well as transport on these rivers emphasizes how innovation plays a role throughout both subjects for this collection. In two articles here, this innovation took the form of the movement of a capitalist, business mentality from the coastal areas, where there was already plenty of seafaring and trade, to the interior via the river. In the eighteenth century, this was the case both along the Rhine and along the Yangtze as can be seen from the articles by Ralf Banken and Yao Chen. The articles by Blussé and Klemann, rather, focus on more concrete technical innovation. Blussé shows how similar circumstances, independently of each other, led to similar technical innovations in the Yangtze and Rhine deltas. Klemann looks at the consequences of nineteenthcentury mechanization for Rhine navigation, especially for the small Rhine skippers.